(untitled) (Baghdad Science Journal, 2011)
This study was designed to know the effect of Diclofenac sodium (voltaren) drug on the histological composition of kidney in domestic rabbits . Twelve adult males with (1.4) kg weight . The first group of animals administrated orally by 1 ml of Voltaren with 6 mg/kg , while the second group with (1) ml of distal water (as control group ) . the administrated continue for (60) days sequentially. The treatment with voltaren showed pathological cases in tissues and cells of kidney including necrosis, infilteration ,congestion in blood vessels edema.Also epithelial separation in kidney tubules in comparison with control group Conclusion from the above results, revealed that voltaren had negative effects on the kidney tissues in local males rabbits .